Oct Angiography: The Basics - Khushboo Chawla (Delhi Journal of Ophthalmology)
OCT angiography is a new imaging technology that provides volumetric analysis of retina, choroid, and optic nerve. It helps to delineate early hemodynamic alteration in the vasculature of retina and choroid. Being non-invasive, OCT A is employed over standard angiographic techniques of fundus fluorescein angiography (FFA) and indocyanine green angiography (ICGA) which study changes in retinal superficial layers and choroid respectively. It gives a high specificity and sensitivity in diagnosis and follow-up of vascular diseases such as diabetic retinopathy, vascular occlusion, and macular degeneration. This article seeks to detail the principle and techniques of OCTA.